Hajj Administration Procedures at the Ministry of Religion in Indonesia - Ibrahim, Naufal (Lead Journal of Economy and Administration, 2022)
The purpose of this study was to find out how the Hajj administration procedures were carried out at the Ministry of Religion, to find out the constraints of the Hajj administrative procedures carried out by the Ministry of Religion and to find out how to solve problems that occurred in the Hajj Administration Procedures at the Ministry of Religion. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the procedures for the administration of hajj at the ministry of religion. In this study, data relating to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the research on Hajj administration procedures at the ministry of religion which is as follows: for information on the departure of the pilgrimage that is fifteen years old, prospective pilgrims can check with the portion number that has been printed on registering for Hajj registration, for bank validation numbers that have passed 7 working days or have expired, it is confirmed that prospective pilgrims when opening Hajj savings accounts do not leave files in the bank, they must wait until the process is complete and prospective pilgrims receive the file and for prospective pilgrims, they must prepare the requirements before registering Hajj with the Ministry of Religion so that data can be input quickly.